Faktor-Faktor yang Mempengaruhi Kepatuhan Wajib Pajak Kendaraan Bermotor di Kota Batam - Dini Aulia; Mortisor Afrizal Purba (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Indonesia, a developing nation, has undertaken extensive development efforts across all sectors to foster a prosperous and thriving community. The tax sector is one of the primary sources of government funds. When we hear the term